Policy Gaps and Opportunities in Bio-Based Plastics: Implications for Sustainable Food Packaging - Walter Leal Filho; Jelena Barbir; Madhavi Venkatesan; Amanda Lange Salvia; Andrea Dobri; Neda Bošković; João Henrique Paulino Pires Eustachio; Ian Ingram; Maria Alzira Pimenta Dinis (Foods)
The increasing use of bio-based and/or biodegradable plastics reflects a global push towards more sustainable materials. In the context of food packaging, where plastic waste and contamination risks are acute, these materials offer promising alternatives. However, the transition is complex, requiring coordinated regulatory interventions and lifecycle assessments (LCA) to avoid unintended environmental and health consequences. This paper outlines the pressing need for policies that guide the development and deployment of bio-based plastics in food-related applications. It provides a policy-oriented synthesis focused on Europe and discusses recent concerns such as toxicity, end-of-life impacts, and food safety. The study draws from the literature review and regulatory analysis to suggest policy mechanisms that can accelerate safe, circular solutions in food packaging. Methodologically, this communication uses qualitative synthesis of scientific and regulatory data to assess gaps and align innovations with sustainability targets.